2019
DOI: 10.1186/s12870-019-2111-5
|View full text |Cite
|
Sign up to set email alerts
|

PdWND3A, a wood-associated NAC domain-containing protein, affects lignin biosynthesis and composition in Populus

Abstract: BackgroundPlant secondary cell wall is a renewable feedstock for biofuels and biomaterials production. Arabidopsis VASCULAR-RELATED NAC DOMAIN (VND) has been demonstrated to be a key transcription factor regulating secondary cell wall biosynthesis. However, less is known about its role in the woody species.ResultsHere we report the functional characterization of Populus deltoides WOOD-ASSOCIATED NAC DOMAIN protein 3 (PdWND3A), a sequence homolog of Arabidopsis VND4 and VND5 that are members of transcription fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 58 publications
(108 reference statements)
1
25
0
Order By: Relevance
“…Overexpression of PtrWND2B and PtrWND6B in Arabidopsis causes ectopic deposition of secondary cell wall through activation of the lignin, cellulose and xylan biosynthetic genes (Zhong et al, 2010b). In Populus, the transcript of CCoAOMT1 was induced by overexpressing WND3A (Yang et al, 2019). Zhou et al (2014) demonstrated that the promoter of CCoAOMT1 is directly activated by Arabidopsis VND1-5.…”
Section: Ccoaomtmentioning
confidence: 98%
“…Overexpression of PtrWND2B and PtrWND6B in Arabidopsis causes ectopic deposition of secondary cell wall through activation of the lignin, cellulose and xylan biosynthetic genes (Zhong et al, 2010b). In Populus, the transcript of CCoAOMT1 was induced by overexpressing WND3A (Yang et al, 2019). Zhou et al (2014) demonstrated that the promoter of CCoAOMT1 is directly activated by Arabidopsis VND1-5.…”
Section: Ccoaomtmentioning
confidence: 98%
“…Likewise, 183 NAC genes were identified in the white pear ( Pyrus bretschneideri ), which were divided into 33 subgroups, out of which the C2f, C72b and C100a subgroups actively responded to drought and low-temperature stress ( Xin et al, 2019 ). With increased research on the biological functions of NAC transcription factors, it has been shown that NAC transcription factors can regulate a wide range of plant life processes including plant growth and development, the growth and senescence of the cell wall and root through plant hormone signaling pathways ( Wei et al, 2018 ; Yongil et al, 2019 ), and improving plant resistance by responding to a variety of abiotic and biological stress factors ( Du et al, 2020 ; Jia et al, 2019 ). In terms of abiotic regulation, the research on the pathways and mechanisms of NAC family genes for abiotic stress has been intensively studied.…”
Section: Discussionmentioning
confidence: 99%
“…The study revealed that cca-miR4391 and cca-miR11300 might inhibit the 'NAC Domain Containing Protein' whereas cca-miR1536, cca-miR4391 and cca-miR8689 might cleave the 'S-adenosyl-l-Met-dependent methyl transferase'. Secondary cell wall formation associated NAC protein and its functional homologues are crucial regulatory points that turn on a subset of transcription factors which also directly activate the expression of SCW biosynthetic genes [28,29]. The diverse variety of Cleavage Lignin biosynthesis process [28,29] Secondary cell wall formation [28,29] S-adenosyl-L-Met-dependent methyl transferase cca-miR1536, cca-miR4391, cca-miR8689…”
Section: Discussionmentioning
confidence: 99%
“…All of the gene targets were cross checked where four gene targets were found as the common target for the five putative miRNAs, and those targets were also highly abundant in the target pool ('Leucine-rich repeat family protein; 13 times', 'Transposable element gene; 87 times', 'Protein kinase superfamily protein; 17 times', 'Pentatricopeptide repeat superfamily protein; 9 times'). Comprehensive literature studies were employed to find out the involvement of predicted gene targets in different biological process.There were few gene targets which were found to be directly or indirectly involved with the lignin biosynthesis and secondary wall biogenesis (Table 3) [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. The functions of the common gene targets were also described in Table 3.…”
Section: Prediction and Functional Analysis Of Putative Mirna Targetsmentioning
confidence: 99%